Advances in Human Factors and Sustainable Infrastructure Proceedings of the AHFE 2016 International Conference on Human Factors and Sustainable Infrastructure, July 27-31, 2016, Walt Disney World®, Florida, USA - Charytonowicz, Jerzy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book deals with human factors research directed towards realizing and assessing sustainability in the built environment. It reports on advanced engineering methods for sustainable infrastructure design, as well as on assessments of the efficient methods and the social, environmental, and economic impact of various designs and projects. The book covers a range of topics, including the use of recycled materials in architecture, ergonomics in buildings and public design, sustainable design for smart cities, design for the aging population, industrial design, human scale in architecture, and many more. Based on the AHFE 2016 International Conference on Human Factors and Sustainable Infrastructure, held on July 27-31, 2016, in Walt Disney World®, Florida, USA, this book, by showing different perspectives on sustainability and ergonomics, represents a useful source of information for designers in general, urban engineers, architects, infrastructure professionals, practitioners, public infrastructure owners, policy makers, government engineers and planners, as well as operations managers, and academics active in applied research.
Keywords: Computational intelligence; Engineering design; Sustainability; Architecture; Buildings; Urban economics; Computational Intelligence; Engineering Design; Sustainability; Building Types and Functions; Urban Economics